2021
DOI: 10.3847/1538-3881/abd177
|View full text |Cite
|
Sign up to set email alerts
|

The TESS–Keck Survey. IV. A Retrograde, Polar Orbit for the Ultra-low-density, Hot Super-Neptune WASP-107b

Abstract: We measured the Rossiter-McLaughlin effect of WASP-107b during a single transit with Keck/HIRES. We found the sky-projected inclination of WASP-107b's orbit, relative to its host star's rotation axis, to bedegrees. This confirms the misaligned/polar orbit that was previously suggested from spot-crossing events and adds WASP-107b to the growing population of hot Neptunes in polar orbits around cool stars. WASP-107b is also the fourth such planet to have a known distant planetary companion. We examined several d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 68 publications
0
28
0
Order By: Relevance
“…Specifically for WASP-107, Anderson et al (2017) reported a K6 host star with a mass of M * = 0.69 M e , a radius of R * = 0.66 R e , and an effective temperature of T *,eff = 4430 K. Planet b orbits its host on a near-circular but polar orbit (Dai & Winn 2017, C. Piaulet et al 2021Rubenzahl et al 2021). The semimajor axis is a = 0.055 au where the equilibrium temperature is T eq = 740 K; the transit light curve indicates a small impact parameter (b = 0.07 Dai & Winn 2017).…”
Section: Basic Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically for WASP-107, Anderson et al (2017) reported a K6 host star with a mass of M * = 0.69 M e , a radius of R * = 0.66 R e , and an effective temperature of T *,eff = 4430 K. Planet b orbits its host on a near-circular but polar orbit (Dai & Winn 2017, C. Piaulet et al 2021Rubenzahl et al 2021). The semimajor axis is a = 0.055 au where the equilibrium temperature is T eq = 740 K; the transit light curve indicates a small impact parameter (b = 0.07 Dai & Winn 2017).…”
Section: Basic Setupmentioning
confidence: 99%
“…Dai & Winn (2017) suspected that the planet is on a polar orbit owing to the lack of repeating spot-crossing events. More recently, a Rossiter-McLaughlin measurement by Rubenzahl et al (2021) confirmed this suspicion and thus demands a dynamically hot formation and evolution pathway that may involve the nontransiting planet 107c (P ∼ 1100 days,M i sin Å M 110 ; C. Piaulet et al 2021). These reasons render WASP-107b a unique and interesting system.…”
Section: Introductionmentioning
confidence: 96%
“…Several exoplanets systems that host spin-orbit misaligned close-in small planets have been found to contain an distant giant planet, e.g., HAT-P-11 (Winn et al 2010;Yee et al 2018), π Men (Jones et al 2002;Kunovac Hodžić et al 2021), Kepler-56 (Huber et al 2013Otor et al 2016), andWASP-107 (Piaulet et al 2021;Rubenzahl et al 2021). Kepler-129 joins their ranks.…”
Section: Comparison To Other Planetary Systemsmentioning
confidence: 99%
“…The alignment between solar spin and planetary orbital axes is considered to result from the protoplanetary disk where these planets formed and has been maintained throughout the history of the solar system (Kant 1755;de Laplace 1796). On the contrary, spin-orbit misalignment has been found in dozens of exoplanet systems (e.g., Winn et al 2010;Huber et al 2013;Bourrier et al 2018;Yee et al 2018;Kamiaka et al 2019;Rubenzahl et al 2021), suggesting a different formation pathway or the occurrence of dynamical events in those systems. Measuring the spin-orbit angle therefore helps to understand the formation and evolution of planetary systems.…”
Section: Introductionmentioning
confidence: 99%
“…TKS is a consortium performing precise RV (PRV) followup of TESS planet candidates (Dalba et al 2020;Dai et al 2020;Rubenzahl et al 2021;Weiss et al 2021). One of our group's primary science goals is to measure a diverse set of planet masses at high enough precision to be suitable for atmospheric characterization (Batalha et al 2019), particularly with the James Webb Space Telescope (JWST), which is what led us to observe HD 63935.…”
Section: Introductionmentioning
confidence: 99%